The Respective Relationship Influence of a Teacher to Pupils in the Process of their Intellectual Independence Formation - Heorhinova, Larysa; Kuryliak, Valentyna (Pedagogical Discourse, 2016)
The article presents the concept of respective attitude. The relationship of parents’ and teachers’ influence on school-age children is given. The justification and the results of the practical manifestations of respective relations of a teacher to pupils at computer science lessons are presented. In the study, an attempt is made to deduce the dependence of students’ intellectual autonomy growth on the respecting relationship of a teacher to them. The attention is focused on the importance of making an individual portrait of a learner, the need to identify factors, which will help him to realize his potential and to increase his interest in the material’s content studied in the classroom. It is proved that students, who are experiencing the systematic respect of a teacher in relation to themselves, begin to show a higher level of independence in performing additional tasks on the subject. It was found that the respective attitude of a teacher is defined as a respectful treatment of all positive results of a student’s activities no matter how much success he achieves. Since the notion of intellectual autonomy is a personal quality associated with the readiness of the pupil to set goals of self-improvement in training activities without any prompting from the outside and to achieve the solutions on his own, then the important factor is his parents support. The experimental data confirmed that the higher performance by teachers may be achieved, if they pay particular attention to this issue in working with pupils of 8-11 classes, i.e. adolescents aged 13-16. Key words: respective attitude, the formation of intellectual independence, the influence of parents, teacher’s respective attitude.